Recovery of uranium from phosphate ore in the Sheikh Habil-Iran mine: part I— multivariable optimization of leaching process using the response surface method - Abdeshahi, A.; Outokesh, M.; Nejad, D. Ghoddocy; Zare, M. Habibi; Sadeghi, M. H. (Frontiers in Chemistry, 2023)
In this research, the recovery of uranium from the phosphate ore of the Sheikh Habil-Iran mine using flotation/calcination-leaching processes has been investigated. A 75–150 μm phosphate ore particle size, sodium oleate as a collector with a concentration of 2,000 g/ton of rock, pH = 10, and 5 min flotation time were obtained as the optimum parameters of flotation using the reverse method, leading to phosphate ore with a grade of 180 ppm UO2, 36.1% P₂O₅, 7.22% SiO2, and CaO/P₂O₅ = 1.23. The optimum calcination parameters were selected as 100 μm phosphate ore particles size at D80, 900°C temperature, and 2 h heating time, which resulted in phosphate ore with a grade of 173 ppm UO2 and 31.9% P₂O₅. An L/S (liquid to solid ratio) = 5, 3 M sulfuric acid concentration, 80°C temperature, and 5 h leaching time were obtained as the optimum leaching parameters using the response surface methodological approach. The efficiency of uranium recovery from phosphate ore pre-treated by flotation and calcination methods was 84.2% and 75.2%, respectively. The results indicated that flotation has superiority over calcination as a pre-treatment method of phosphate ore in the Sheikh Habil-Iran mine.